Currículo integrado e formação continuada de professores: a abordagem CTS como articuladora do processo - Lacerda, Caroline Côrtes (2018)
A research project as a research concept of curriculum concepts, as as contributions and challenges of a proposal of continuing education for educators, on the web, in the area of Science Technology Society (STS), with regard to the development of experiences curriculum. The work is organized in four articles and was developed with a qualitative and descriptive approach or also called field research. For an implementation was obtained the voluntary participation of educators who answered a questionnaire applied in the first phase of the investigation, and that enabled to diagnose the researched reality. In the second phase, also a voluntary subgroup of educators who had participated in the first phase participated in a process of ongoing in-service training in the blended mode. In this scenario, we sought the conceptions of curriculum, without pedagogical thinking of Basic Education teachers. There were no educators who expressed exclusive agreement as ideas of any of the Theories. With this, it was possible to identify that there is not a single conception of curriculum that beacon as teacher conceptions, what is understood as a period of educational ideological transformation. It was analyzed how the educators feel the protagonists of the school curriculum and proposed a reflection on the aspects that involve the construction, participation, execution and monitoring of the school curriculum. Identify that educators realize they can go beyond executing the curriculum and that other people at school can also be held accountable for curriculum processes. There was also discontent among the group about the curriculum planned without their participation, which the teacher puts as a curriculum builder and accepts the importance of the community in the process. It was sought to identify how pedagogical practices carried out by educators are directed towards a conception of integrated curriculum as subjects. STS can be process transformation agents. In this aspect, it can be seen that the main form of realization was the approximation of contents with the daily life of the students, followed by the interdisciplinary approach and didactic methodologies. As the most frequent difficulties, in the realization of the Integrated Curriculum, are a lack of motivation and a space between the peers, a lack of time, meetings of planning and dialogue between like areas and lack of continuous formation. In addition, there was a simplification in the speech of the educators when referring to the STS approach, because they reduce the issues related to electronic technological devices. In view of the diagnosis of the investigated reality, we sought to analyze the perception of Basic Education educators about the accomplishment of a semipresencial course, as well as limits and potentialities for the continuous formation. In the face-to-face session, everyone presented orally several experiences, and the moment was opportune for some educators to know the work of the other, since there are some who were little in the function according to the schedules. In the distance part, it was verified the lack of specific time in the working hours for an accomplishment of the activities and a resistance to the use of the virtual environment of learning. However, a lack of time for a key element to a drop out, since it is a closer part and more a demand for work for the teacher. This fact evidences the need for space and time for a documented formation, a workload, even if it is a distance course